Sanctum of the Bhairon shrine on Harsha Hill - Temples of India Project Team (Jio Institute, 2024)
Close to the Harshnath Temple complex lies the Bhairon shrine featuring a semi-iconic rock revered locally as the Harsha Bhairon. He is believed to be a manifestation of the folk hero, Harsha, who decided to settle at the hill to worship Shiva. He is believed to have been blessed by Shiva to be worshipped as Bhairon on the hill. Several 10th-century CE sculptures are fixed on the walls of this complex. Today, the Bhairon shrine is the epicentre of pilgrimage to Harsha Hill and is considered as the family deity of several local communities.